2018
DOI: 10.1007/s00701-018-3732-4
|View full text |Cite
|
Sign up to set email alerts
|

Impact of intraoperative stimulation mapping on high-grade glioma surgery outcome: a meta-analysis

Abstract: BackgroundIntraoperative stimulation mapping (ISM) using electrocortical mapping (awake craniotomy, AC) or evoked potentials has become a solid option for the resection of supratentorial low-grade gliomas in eloquent areas, but not as much for high-grade gliomas. This meta-analysis aims to determine whether the surgeon, when using ISM and AC, is able to achieve improved overall survival and decreased neurological morbidity in patients with high-grade glioma as compared to resection under general anesthesia (GA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
58
1
5

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 92 publications
(68 citation statements)
references
References 24 publications
4
58
1
5
Order By: Relevance
“…In the present study, we assessed the impact of preoperative KPS and ASA scores on perioperative complications in patients undergoing repeated glioma resection. In contrast with the results reported in the literature for patients with newly diagnosed glioma undergoing primary craniotomy [4,[9][10][11], we did not find any significant correlation between low KPS or high ASA score and perioperative complications, including severe complications (death within 30 days or unplanned reoperation within 7 days), CNS complications, and total complications.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…In the present study, we assessed the impact of preoperative KPS and ASA scores on perioperative complications in patients undergoing repeated glioma resection. In contrast with the results reported in the literature for patients with newly diagnosed glioma undergoing primary craniotomy [4,[9][10][11], we did not find any significant correlation between low KPS or high ASA score and perioperative complications, including severe complications (death within 30 days or unplanned reoperation within 7 days), CNS complications, and total complications.…”
Section: Discussioncontrasting
confidence: 99%
“…The surgical pathway for the repeated operation was usually primary skin and skull incisions and a similar or same pathway to decrease damage, which was one of the risk factors for wound-related complications, including CSF leakage and intracranial infections [2]. In the literature, low KPS is one of the established risk factors for perioperative complications in patients with glioma who undergo craniotomy [4,[9][10][11]. However, most of these studies focused on primary gliomas or gliomas without clarification of recurrence status.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Only very few studies have reported the use of AC in GBM [26,27]. We recently showed in a meta-analysis and a retrospective matched case-control study that patients with GBM operated with AC had less early postoperative neurological morbidity and significantly higher percentage of total resection [28,29]. AC could thus be of high value in the surgical treatment of GBM in eloquent areas.…”
Section: Introductionmentioning
confidence: 99%
“…The widespread introduction of awake craniotomy surgery with ESM has greatly improved the intra-operative identification of eloquent brain areas adjacent to tumors. Intra-operative use of ESM to remove low- (De Witt Hamer et al, 2012) or HGGs (Gerritsen et al, 2019) has been associated with fewer post-operative complications and higher percentages of GTRs. However, ESM also presents with a range of its own inherent limitations, including lack of (sulcus-)depth resolution (Imbault et al, 2017), functional over-estimation due to current leakage (Ritaccio et al, 2018), lack of standardization of stimulation protocols (Pouratian et al, 2004;Ritaccio et al, 2018) and the risk of eliciting epileptic seizures (Su and Ojemann, 2013;Ritaccio et al, 2018).…”
Section: Introductionmentioning
confidence: 99%